Jerusalemites and the Issue of Citizenship in the Context of Israeli Settler-Colonialism - Salem, Walid (Journal of Holy Land and Palestine Studies, 2018)
This article aims to unmask the relationship between the Zionist settler-colonial project and its policies towards the citizenship of the indigenous Palestinian population of East Jerusalem. The article analyses Zionist citizenship politics in detail and how they play together the role of destroying the three (legal, national belonging, and societal membership) dimensions of citizenship for the Palestinians in East Jerusalem. I argue that settler-colonialism presents a more accurate typology for the analysis of the situation in Jerusalem in comparison to the other typologies of equality, occupation, neocolonialism, ethnocracy and open ethnocracy.